O universo infantil e escolar em poesias infantis, de Olavo Bilac - Silva, Ana Paula Serafim Marques da (2018)
In addition to the representation of the school space and the dissemination of values linked to the First Republic in Brazil (1889-1930), the aim of this study was to investigate the attendance of aesthetic care aimed at the formation and delight of the young reader in poetic work Poesias infantis (1904), by the fluminense writer Olavo Bilac. Consecrating the Brazilian poetic discourse, the collection, which was written, architected and published for school purposes, encompasses the sociocultural and pedagogical values propagated during the implantation of the Brazilian republican regime, the contours of our education, the valorization of the national memory and the marks early childhood literature. A bibliographic, documentary and interpretative research, which sought to examine in some poems, illustrations and fables the intellectual, aesthetic and cultural formation of the children and youth public in the late nineteenth and early twentieth centuries. For this, we investigated the social, political and cultural facts that involved the origin of literature for children, presenting, above all, verse production in the national context. We also explore thematic and formal aspects of the fables present in the selection, trying to understand the insertion of another poetic didactic genre, which converges with the educational and literary intention of the corpus. We recognize, throughout the research, the utilitarian purpose of the print and that, in the midst of the pedagogical ideology, there are poems that detach themselves from the pragmatism contained in the copy, revealing lyricism and aesthetic as the sole reason for appreciation, its readers contact with other forms of arts, such as theater and dance. In order to base our work, we mainly use Coelho (2000; 2010), Arroyo (1952; 2011), Lajolo (1982), Pinheiro Alves (2012) and Lajolo & Zilberman (1987) relationship with the target audience.